2014
DOI: 10.1159/000358671
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of miR-141 Induced by Helicobacter Pylori Promotes the Invasion of Gastric Cancer by Targeting STAT4

Abstract: Background: The association between Helicobacter pylori infection and gastric cancer has been identified recently. However, the molecular mechanism remained largely unknown. Methods and Results: We found that miR-141 was decreased in Helicobacter pylori positive specimens (n=75) compared with negative tissues (n=75). The knockdown of miR-141 enhanced the invasion ability of gastric cancer cells; meanwhile, over-expression of miR-141 could inhibit the abilities of gastric cancer cells in vitro. A luciferase ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…H. pylori CagA induces aberrant epigenetic silencing of let-7 expression, leading to Ras upregulation, and thus lead to GC [17]. Our previous study showed that miR-141 acted as a tumor suppressor in human GC by targeting signal transducer and activator of transcription 4 (STAT4) [19]. Mei et al [20] showed that miR-141 expression was significantly up-regulated in NSCLC tissues, and its overexpression accelerated NSCLC cell proliferation in vitro and tumor growth in vivo by targeting PHLPP1 and PHLPP2.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori CagA induces aberrant epigenetic silencing of let-7 expression, leading to Ras upregulation, and thus lead to GC [17]. Our previous study showed that miR-141 acted as a tumor suppressor in human GC by targeting signal transducer and activator of transcription 4 (STAT4) [19]. Mei et al [20] showed that miR-141 expression was significantly up-regulated in NSCLC tissues, and its overexpression accelerated NSCLC cell proliferation in vitro and tumor growth in vivo by targeting PHLPP1 and PHLPP2.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequences of specific primers for the selected genes were as follows: RNF43 forward primer: (5-AGCATGAGTGGTGGCCACCAG-3), reverse primer (5-ATCTCACACAGCCTGTTCAC-3); and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) forward primer: (5-CCACCCATGGCAAAATTCCATGGCA-3), reverse primer: (5-TCTAGACGGCAGGTCAGGTCCACC-3). The relative values of the expressions of the transcripts were calculated using the 2 - ∆∆ C (T) method [11,12]. The mRNA expression level of RNF43 was normalized to that of GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, miR-21 has been found to be overexpressed in GC and to promote tumor proliferation and invasion by negatively regulating important tumor suppressor genes such as PTEN, PDCD4, and RECK [19,20,21]. By contrast, overexpression of miR-141 could suppress GC cell invasion by directly repressing STAT4 [22]. However, it remains unclear whether miRNAs can regulate the expression of FOXQ1 in GC; therefore, we aimed to determine the target miRNAs of FOXQ1.…”
Section: Introductionmentioning
confidence: 99%